A Quantitative Geomorphological Analysis of Beach Sediments Along the Kanthi Coast of West Bengal and Odisha, India - Nayan Dey; Payel Das (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
This research paper shows the beach segment-wise (viz., nearshore, surfing, sub-aerial, and backshore) textural characteristics and their impact on the formation of beach profiles. The grain size of the sediments is the most influential factor in the analysis of the geomorphological structure of sedimentation. The energy which is generated by waves and the grain size of sediments can change the structural pattern of the coastal beach. So it is obvious to study sedimentary textural distribution to know their influence on making coastal beaches. Through this research paper, the sedimentary textual distribution is analyzed and also gives their impact on beach shipping. Along longitudinal beach profile samples are collected. The work has been done based on the primary data source by using the field survey method. From this research work, it has been traced that beaches follow the concave pattern profile due to their fine sedimentary textural distribution. Consequently, the beaches of the Kanthi coast are dominantly facing the erosional configuration.